Alternative Approach toward the Generation of Benzylic Zinc Reagent: Direct Oxidative Addition of Active Zinc into the Carbon–Oxygen Bond of Benzyl Mesylates - Jung, Hye-Soo; Kim, Seung-Hoi (Synlett, 2015)
The use of highly active zinc, prepared by the Rieke method, for the direct preparation of benzylic zinc mesylate was investigated. The oxidative addition of highly active zinc to benzyl mesylate was easily completed under mild conditions. The resulting benzylic zinc mesylates were employed in subsequent cross-coupling reactions with a broad range of electrophiles, and the formation of the corresponding products was successful.
Keywords: benzylic zinc; benzyl meslate; active zinc; oxidative addition; cross-coupling